Laparoscopic surgery for massive ovarian edema during pregnancy: A case report - Shoko Saito; Megumi Yamamoto; Shizuha Iwaizumi; Hiroshi Yoshida; Hiroyuki Shigeta (Elsevier, 2021)
Massive ovarian edema (MOE) is a rare non-neoplastic clinicopathologic disease that is characterized by stromal edema and is caused by the partial or intermittent obstruction of venous and lymphatic drainage. The literature on MOE contains approximately 200 cases, but only 12 cases of MOE during pregnancy have been reported to date.We report a case of MOE at 22 weeks of gestation that was diagnosed preoperatively, and the patient underwent laparoscopic surgery. Accurate preoperative diagnosis of MOE is important because it enables the selection of a therapeutic option, such as fundamental surgery, including adnexectomy; conservative surgery, including the release of torsion and ovarian biopsy; and conservative treatment without surgery.MOE should be considered as a differential diagnosis for an enlarged ovary during pregnancy. Laparoscopic surgery may be a useful therapeutic option for MOE, especially during pregnancy.